India–China Relations: Putting the Record Straight. (June 2019) - Bhattacharya, Abanti
Tansen Sen, India, China, and the World: A Connected History (New Delhi: Oxford University Press, 2018). Pp. 541, ₹770 (Paperback), ISBN 0-19-948554-2. Berenice Guyot-Rechard, Shadow States: India, China and the Himalayas, 1910–1962 (Delhi: Cambridge University Press, 2017). Pp. 321, ₹550 (Paperback), ISBN 978-1-108-40131-9. Bertil Lintner, China's India War: Collision Course on the Roof of the World (New Delhi: Oxford University Press, 2018). Pp. 320, ₹675 (Hardcover), ISBN 0-19-947555-5.